ANALYSIS OF COLLABORATIVE PROBLEM SOLVING LEARNING IN 9 NAMANG PRIMARY SCHOOLS, CENTRAL BANGKA DISTRICT - Imran Imran; Muh. Misdar; Rada Rada (JURNAL EDUSCIENCE, 2024)
This research aims to analyze Collaborative Problem Solving (CPS) learning at Elementary School 9 Namang, Central Bangka Regency. Analysis uses qualitative analysis techniques with the Miles and Huberman model. The analysis is divided into 3 (three), namely: project, case and simulation-based Collaborative Problem Solving (CPS) learning. The sample in this study consisted of one school principal and 8 class teachers. The results of this research are that in project-based Collaborative Problem Solving (CPS) learning practices, the main obstacles faced by teachers are mainly related to class I, where students are still learning to read and write, experiencing a lack of attention and focus. However, progressive development is seen from class III to class VI, where students are faced with increasingly complex challenges, such as designing projects that are relevant to the curriculum and looking for project ideas from literature. In sixth grade, students engage in thorough evaluation of project ideas, selecting the best solution, and planning concrete steps for implementation. Case-based Collaborative Problem Solving (CPS) learning is designed to develop critical thinking and problem solving skills along grade levels. Simulation-based Collaborative Problem Solving (CPS) learning in grades I-VI takes students through a series of progressive stages, starting from simple games that emphasize cooperation to real-world situations using technology and role-playing. This research provides in-depth insight into the implementation of various Collaborative Problem Solving (CPS) methods in educational contexts, with an emphasis on developing students' skills over time.